Boronic Acid Homopolymers as Effective Polycations for Sugar-Responsive Layer-by-Layer Assemblies - Florea, Larisa; Delaney, Colm (My University, 2019)
Due to their reversible diol-binding ability, phenylboronic acid (BA) derivatives have gained considerable interest for the development of saccharide sensors and drug delivery systems. In particular, BA-containing polymers have been used for the realisation of sugar-responsive layer-by-layer (LbL) films. Herein, a LbL system based on cationic BA-homopolymers (PBA) is presented, and its subsequent sugar-induced disassembly is described. The BA-linear polymers (PBA) were intercalated with poly(vinylsulfonic acid, sodium salt) to form (PBA/PVS), film assemblies. Different orientations of the boronic acid substituent (ortho-, meta-and para-) in the PBA polymer were investigated for their influence on the LbL assembly. The rate of disassembly in the presence of glucose or fructose was analyzed by UV-vis spectroscopy. Additionally, the PVS component was replaced by an anionic fluorophore, pyranine (PYR), which allowed the assembly and disassembly to be monitored by fluorescence.
PUBLISHED
Keywords: Layer-by-layer; Boronic acid; Fluorescence; Fructose; Pyranine; Stimuli-responsive; Nanoscience & Materials; BORONIC ACIDS; Layer-by-Layer; Polymers; SENSORS; Sugar